Analyzing Pre-Service English Teachers' Digital Literacy Skills in EFL Teaching - Zahraini Fajri Nur; Sahril Nur; La Sunra (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study analyses the types of digital literacy skills frequently used and how digital literacy skills support pre-service English teachers’ performances. This research used a mixed method with an explanatory sequential design. The data collection method begins with the collection of quantitative data by online questionnaire, then proceed with the collection of qualitative data to help analyze the data obtained quantitatively through observation and interview. The population of this study was pre-service English teachers, the sixth-semester students of the English Education program at Universitas Negeri Makassar who program teaching training including PPL, Kampus Mengajar, and Ajarmi program. One hundred and two pre-service English teachers filled out the questionnaire, while several representatives were chosen for interview. The result showed that (1) various digital literacy skills were used by pre-service English teachers, such as information, technology, media, communication, reproduction, branching, socio-emotional, and real-time thinking skills. However, the use of information literacy has the highest used percentage, which is 54 % in Often category and 0 % in Never category. and (2) pre-service English teachers' use of digital literacy skills supported the teaching performances, including the access to prepare teaching models and media, improving their teaching skills, and producing new creative and innovative teaching content.